Spontaneous regression of an isolated retinal astrocytic hamartoma in a newborn: a case report - Bo Yang; Danfeng Li; Jun Xiao (BMC Ophthalmology, 2023)
Abstract Background To report the spontaneous regression of an isolated retinal astrocytic hamartoma in a newborn. During the seven-month follow-up duration, fundus photography and fluorescein angiography examinations were performed. Case presentation An isolated retinal astrocytic hamartoma was detected in the nasal retina of the left eye of a 4-day-old male infant. At the time of initial presentation, we detected a solitary yellowish-white flat mass with an approximate size of 1.5 disc diameters in the nasal retina. Fluorescein angiography (FA) revealed a diffuse hyperfluorescence with slight fluorescence leakage. Seven months later, the fundus examination showed no lesion in the left eye, FA revealed mild tortuous vessels without leakage. Conclusions In the present case, we established that the isolated retinal astrocytic hamartoma in this infant has underwent spontaneous regression. This case can point out that follow –up reexaminations are advisable for a solitary yellowish-white flat mass of the fundus in a newborn.